Maternal Gestational Hypertension-Induced Sensitization of Angiotensin II Hypertension Is Reversed by Renal Denervation or Angiotensin Converting Enzyme Inhibition in Rat Offspring - Xue, Baojian (Hypertension, 2017)
Numerous findings demonstrate that there is a strong association between maternal health during pregnancy and cardiovascular disease in adult offspring. The purpose of the present study was to test whether maternal gestational hypertension modulates brain renin-angiotensin-aldosterone system (RAAS) and proinflammatory cytokines that sensitizes angiotensin II-elicited hypertensive response in adult offspring. Also, the role of renal nerves and the RAAS in the sensitization process was investigated. RT-PCR analyses of structures of the lamina terminalis and paraventricular nucleus indicated upregulation of mRNA expression of several RAAS components and proinflammatory cytokines in 10-week old male offspring of hypertensive dams. Most of these increases were significantly inhibited by either renal denervation performed at 8 weeks of age or treatment with an angiotensin converting enzyme inhibitor, captopril, in drinking water starting at weaning. When tested beginning at 10 weeks of age, a pressor dose of angiotensin II resulted in enhanced upregulation of mRNA expression of RAAS components and proinflammatory cytokines in the lamina terminalis and paraventricular nucleus and an augmented pressor response in male offspring of hypertensive dams. The augmented blood pressure change and most of the increases in gene expression in the offspring were abolished by either renal denervation or by captopril. The results suggest that maternal hypertension during pregnancy enhances pressor responses to angiotensin II through overactivity of renal nerves and the RAAS in male offspring, and that upregulation of the brain RAAS and proinflammatory cytokines in these offspring may contribute to maternal gestational hypertension-induced sensitization of the hypertensive response to angiotensin II.